Analisis Kinerja Pendapatan Industri Perbankan Syariah di Indonesia - Muhammad Syaifulloh; Imam Asngari; Ahmad Syathiri (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to obtain empirical evidence regarding the analysis of the revenue performance of the Sharia Banking industry in Indonesia. This research uses panel data. The number of banks studied were 10 Sharia Commercial Banks in Indonesia listed in the 2015-2022 Sharia Banking Statistics. The variables used in this research are Income (Ln_Income), Capital (Ln_Modal), Murabahah Financing (P_M), Operational Costs Operational Income (BOPO) Ratio (RBOPO), Dummy Covid-19 (DCovid19). Based on the results of statistical testing using eviews 12, the Capital and Covid 19 Dummy variables have an effect on Islamic bank revenues, while the Murabahah Financing variables, BOPO Ratio have no effect on Revenues of Sharia Commercial Banks in Indonesia. Results The coefficient of determination (R2) is 0.885. This explains that the influence of the independent variable on the dependent is 88.5% and the remaining 11.5% is influenced by other variables not examined in this research.